Mean-field polycrystal plasticity modeling with grain size and shape effects for laser additive manufactured FCC metals. (1st May 2017) - Liu, Jian; Xiong, Wei; Behera, Amit; Thompson, Sean; To, Albert C.
Abstract: Additive manufacturing (AM) (also called 3D printing) process has the unique ability to produce very different microstructural features and mechanical properties in metals using the same feedstock material but different process parameters. A common microstructural feature of AM parts is elongated grains along the build direction with a strong crystallographic texture. The goal of this paper is to establish a modeling tool capable of predicting mechanical properties (strength and anisotropy) from the microstructure features (texture, grain size, shape) of AM metals. To achieve this goal, the effect of grain size and shape was incorporated into the mean field polycrystal plasticity modeling framework. Three case studies were performed on general FCC metals with three different ideal microstructures to demonstrate the coupled effect of grain size, shape and texture in the proposed polycrystal plasticity model. Finally, model validation and parameter calibration were performed for AM AlSi10Mg printed using the EOS DMLS (direct metal laser sintering) system.